The Effect Of 30-Degree Head Elevation In Patients With Post-Craniotomy Sol Diagnosis On Improving Cerebral Tissue Perfusion In The Intensive Care Unit (ICU) - Nova Nova; Hikmat Pramajati; Nenden Rostini Hidayat (Jurnal Ners, 2025)
Intracranial Space Occupying Lesion (SOL) after craniotomy poses a risk of impaired cerebral perfusion due to increased intracranial pressure (ICP). One of the non-invasive interventions is the 30° head elevation position. This study aims to determine the effect of 30-degree head elevation position on improving cerebral tissue perfusion in post-craniotomy SOL patients. The method used is Case Report evidence-based nursing care on one patient in the ICU at Umar Wirahadikusumah Hospital. The 30° head elevation intervention was carried out for four days, each 2 hours per day, with monitoring of GCS, MAP, and oxygen saturation. The results showed an improvement in consciousness status from GCS E4M5V4 to E4M6V5, a decrease in MAP from 123 mmHg to 93 mmHg, and an increase in SPO2 from 90% to 97%. It was concluded that 30° head elevation was effective in increasing cerebral perfusion, decreasing ICP, and improving the patient's neurological condition. This intervention is recommended as a standard procedure in critical care nursing for post-craniotomy patients.